Case report: Intracranial lesions of cat-scratch disease mimicking an atypical meningioma - Fang, Qiang; Wang, Pengju; Qin, Shanshan; Liu, Shangxin; He, Jingzhen (Frontiers in Neurology, 2023)
Objectives: Cat-scratch disease (CSD) is an infectious disease caused by Bartonella henselae. The most typical symptom of patients with CSD is regional lymphadenopathy, while central nervous system lesions related to CSD are rare. Here, we present a case of an aged woman with CSD involving the dura matter with a manifestation similar to that of an atypical meningioma. Methods: The patient was followed up by our neurosurgery and radiology teams. Clinical information was recorded, and the pre-operation and post-operation CT results and magnetic resonance imaging (MRI) changes were collected. The paraffin-embedded tissue was sampled for polymerase chain reaction (PCR) test. Results: In this article, we presented details of a 54-year-old Chinese woman admitted to our hospital for paroxysmal headache for 2 years that worsened in the past 3 months. Brain CT and MRI showed a meningioma-like lesion below the occipital plate. En bloc resection of the sinus junction area was performed. Pathological examination showed granulation tissue and fibrosis with acute and chronic inflammation, granuloma and central stellate micro-abscess, which was suspected as cat-scratch disease. The paraffin-embedded tissue was sampled for polymerase chain reaction (PCR) test to amplify the corresponding pathogen genes sequence, which was Bartonella henselae. Conclusion: The case in our study underscores the fact that the incubation period of CSD may be very long; on the other hand, CSD can involve the meninges, resulting in tumor-like lesions.